Association Analysis And Selection Strategies For Various Yield Contributing Traits In Rice Genotypes (Applied Biological Research, 2017)
Genetic differences between rice genotypes were analyzed to assess genetic  association between grain yield and yield contributing traits as a basis for  selection of high yielding rice genotypes. Forty-two rice genotypes were  evaluated for 11 quantitative traits to decide selection criteria under sandy  loam soil conditions at Northern Hill Zone of Chhattisgarh (India). Results  revealed enough variability in genotypes. Genotypic coefficient of variation  was highest in grains panicle-1 (22.02), followed by spikelet fertility (18.30),  spikelets panicle-1 (17.11), yield (15.395 kg ha-1). High estimates for heritability  was exhibited by spikelet fertility (99.84) followed by days to 50% flowering  (98.39), days to maturity (95.75), plant height (79.08). The number of grains  panicle-1 showed highest positive direct effect (4.88) on grain yield followed by  plant height (0.476), spikelet fertility (0.29) and days to 50% flowering (0.21).  The characters showing high heritability coupled with high genetic advance  and significant correlation with yield contributing traits may be used as  selection criteria for grain yield under sandy loam soil conditions.
Keywords: Correlation analysis; genetic variability; path analysis; rice